Philosophy of education in a new key: Who remembers Greta Thunberg? Education and environment after the coronavirus. Issue 14 (6th December 2021) - Jandrić, Petar; Jaldemark, Jimmy; Hurley, Zoe; Bartram, Brendan; Matthews, Adam; Jopling, Michael; Mañero, Julia; MacKenzie, Alison; Irwin, Jones; Rothmüller, Ninette; Green, Benjamin; Ralston, Shane J.; et al.
Abstract: This paper explores relationships between environment and education after the Covid-19 pandemic through the lens of philosophy of education in a new key developed by Michael Peters and the Philosophy of Education Society of Australasia (PESA). The paper is collectively written by 15 authors who responded to the question: Who remembers Greta Thunberg? Their answers are classified into four main themes and corresponding sections. The first section, 'As we bake the earth, let's try and bake it from scratch', gathers wider philosophical considerations about the intersection between environment, education, and the pandemic. The second section, 'Bump in the road or a catalyst for structural change?', looks more closely into issues pertaining to education. The third section, 'If you choose to fail us, we will never forgive you', focuses to Greta Thunberg's messages and their responses. The last section, 'Towards a new (educational) normal', explores future scenarios and develops recommendations for critical emancipatory action. The concluding part brings these insights together, showing that resulting synergy between the answers offers much more then the sum of articles' parts. With its ethos of collectivity, interconnectedness, and solidarity, philosophy of education in a new key is a crucial tool for development of post-pandemic (philosophy of) education.